2015
DOI: 10.5507/bp.2015.055
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of valproic acid during delivery in mothers and in umbilical cord - correlation with birth length and weight

Abstract: Aims. The data on the valproic acid transplacental transfer and risk to the fetus of exposure, remain sparse and only a limited number of studies have reported umbilical cord blood levels. Materials and Methods. Maternal and umbilical cord serum levels were analyzed at delivery in a cohort of 58 women, between the years 1991 -2013. The request forms for routine therapeutic drug monitoring were used as the data source. Maternal levels and dosing information were used for estimating the maternal apparent oral cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
3
18
2
Order By: Relevance
“…Other new findings included an increased height and decreased head circumference/height index in the exposed group. VPA exposure has been associated with low birth weight and length (Kacirova et al, 2015) but not, to our knowledge, with increased height. A decreased head circumference/height index has also not been previously observed.…”
Section: Discussioncontrasting
confidence: 62%
“…Other new findings included an increased height and decreased head circumference/height index in the exposed group. VPA exposure has been associated with low birth weight and length (Kacirova et al, 2015) but not, to our knowledge, with increased height. A decreased head circumference/height index has also not been previously observed.…”
Section: Discussioncontrasting
confidence: 62%
“…12,14 This has not been assessed in the present study, but extensive variability was recently demonstrated in 58 women where maternal and umbilical cord concentrations of VPA were measured, where neonatal length and weight were inversely correlated to exposure, that is, to concentration, but not to the dosage. 15 This important finding was made in the only study so far where TDM has been used during pregnancy to study exposure of VPA and outcome in the offspring. In a retrospective and natural, setting there are limitations that are difficult to control for.…”
Section: Discussionmentioning
confidence: 94%
“…All AED measurements were performed using standard validated methods: high‐performance liquid chromatography for LTG, CBZ and its active metabolite carbamazepine‐10,11‐epoxide (CBZ‐E), and LEV and gas‐liquid chromatography for TPM and VPA . All methods participated in externally quality control schemes.…”
Section: Methodsmentioning
confidence: 99%
“…All AED measurements were performed using standard validated methods: high-performance liquid chromatography for LTG, CBZ and its active metabolite carbamazepine-10,11epoxide (CBZ-E), and LEV 15 and gas-liquid chromatography for TPM 16 and VPA. 17 All methods participated in externally quality control schemes. LTG, LEV and TPM: Instand eV, Gesellschaft zur Förderung der Qualitätssicherung in medizinischen Laboratorien eV; CBZ and VPA: RfB Referenzinstitut für Bioanalytik.…”
Section: Analysis Of Aed Plasma Levelsmentioning
confidence: 99%